Melatonin for premenstrual syndrome: A potential remedy but not ready - Yin, Wei; Zhang, Jie; Guo, Yao; Wu, Zhibing; Diao, Can; Sun, Jinhao (Frontiers in Endocrinology, 2023)
Premenstrual syndrome (PMS), a recurrent and moderate disorder that occurs during the luteal phase of the menstrual cycle and quickly resolves after menstruation, is characterized by somatic and emotional discomfort that can be severe enough to impair daily activities. Current therapeutic drugs for PMS such as selective serotonin reuptake inhibitors are not very satisfying. As a critical pineal hormone, melatonin has increasingly been suggested to modulate PMS symptoms. In this review, we update the latest progress on PMS-induced sleep disturbance, mood changes, and cognitive impairment and provide possible pathways by which melatonin attenuates these symptoms. Moreover, we focus on the role of melatonin in PMS molecular mechanisms. Herein, we show that melatonin can regulate ovarian estrogen and progesterone, of which cyclic fluctuations contribute to PMS pathogenesis. Melatonin also modulates gamma-aminobutyric acid and the brain-derived neurotrophic factor system in PMS. Interpreting the role of melatonin in PMS is not only informative to clarify PMS etiology but also instructive to melatonin and its receptor agonist application to promote female health. As a safe interaction, melatonin treatment can be effective in alleviating symptoms of PMS. However, symptoms such as sleep disturbance, depressive mood, cognitive impairment are not specific and can be easily misdiagnosed. Connections between melatonin receptor, ovarian steroid dysfunction, and PMS are not consistent among past studies. Before final conclusions are drawn, more well-organized and rigorous studies are recommended.